A Critical Review of International Studies into Citizenship and Citizenship Education - Lessons for Citizenship Education in Slovenia - Tit Neubauer (Journal of Social Science Education, 2012)
Referring to a critical review of eight international research initiatives (e.g. studies, surveys, research reports) conducted between 2001 and 2010 in the field of citizenship and citizenship education, this paper examines the relationship between different conceptualisations of citizenship and the nature, role and impact of citizenship education. I focus on the European aspects of these research initiatives and draw on the knowledge they disseminate to reflect on the theory of citizenship and the practice of citizenship education in Slovenia. First, I present an overview of the methodology used in the literature review and reflect on the significant limitations in conducting international and comparative research. Second, I reflect on the various relationships between different conceptualisations of citizenship and their effects on citizenship education practices as presented in the overviewed literature. On the basis of the knowledge and results of the literature review, I then make several observations which are relevant to the advancement of citizenship theory and citizenship education practice in Slovenia. Finally, I argue that different conceptualisations of citizenship can have a significant influence on the practice of citizenship education, as evinced by the analysis of the recent results on civic knowledge in Slovenia.